2012
DOI: 10.1098/rspb.2011.2485
|View full text |Cite
|
Sign up to set email alerts
|

The sound of one-hand clapping: handedness and perisylvian neural correlates of a communicative gesture in chimpanzees

Abstract: Whether lateralization of communicative signalling in non-human primates might constitute prerequisites of hemispheric specialization for language is unclear. In the present study, we examined (i) hand preference for a communicative gesture (clapping in 94 captive chimpanzees from two research facilities) and (ii) the in vivo magnetic resonance imaging brain scans of 40 of these individuals. The preferred hand for clapping was defined as the one in the upper position when the two hands came together. Using com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 79 publications
5
44
0
1
Order By: Relevance
“…Hopkins and his colleagues (Cantalupo and Hopkins 2001;) and others (e.g., Gannon et al 1998) have demonstrated that these "language" areas can be identified in the brains of great apes, and they are also asymmetrically larger, on average, in the left cerebral hemispheres of these close human relatives, although not every study of Broca's area homologues in great ape brains finds this asymmetry, suggesting that the degree of asymmetry, here, is less robust in great apes than in humans (e.g., Meguerditchian et al 2012;Schenker et al 2010). In related work, there is some evidence that chimpanzees display a weak but significant right-hand bias for bimanual grooming, implicating a left-hemisphere dominance for this activity (e.g., Hopkins et al 2007a).…”
Section: Evidence From Cerebral Asymmetriesmentioning
confidence: 94%
“…Hopkins and his colleagues (Cantalupo and Hopkins 2001;) and others (e.g., Gannon et al 1998) have demonstrated that these "language" areas can be identified in the brains of great apes, and they are also asymmetrically larger, on average, in the left cerebral hemispheres of these close human relatives, although not every study of Broca's area homologues in great ape brains finds this asymmetry, suggesting that the degree of asymmetry, here, is less robust in great apes than in humans (e.g., Meguerditchian et al 2012;Schenker et al 2010). In related work, there is some evidence that chimpanzees display a weak but significant right-hand bias for bimanual grooming, implicating a left-hemisphere dominance for this activity (e.g., Hopkins et al 2007a).…”
Section: Evidence From Cerebral Asymmetriesmentioning
confidence: 94%
“…[52][53][54][55][56][57], others have reported right-hand biases in chimpanzees (Pan troglodytes) for: bimanual feeding, coordinated bimanual actions, bipedal reaching and throwing [for reviews, see 58,59], in captive gorillas for bimanual feeding [60] and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 for communicative gesture in chimpanzees [e.g. 10,61,62]. Alternatively, it has been noted that orangutans a exhibited a significant left-hand preference for scratching and for fine manipulation of parts of the face in rehabilitated orangutans [63], while chimpanzees exhibited a significant increase in left-handed self-directed behaviors with increased in task complexity [64] contending that self-directed behaviors may be influenced by motivational factors underpinned by a right hemisphere dominance within both social and nonsocial contexts.…”
mentioning
confidence: 99%
“…Furthermore, the direction of hand preference for clapping explains a significant portion of the variability in asymmetries of the planum temporale and inferior frontal gyrus [30] . In contrast, no signifi cant population-level cerebral structural asymmetries have been reported in the macaque, except for the surface area of the superior temporal sulcus [31] .…”
Section: Asymmetries In the Human Brain And In Our Primate Relativesmentioning
confidence: 99%
“…Chimpanzees, our closest relatives, show both a bias towards right-handedness at the population-level [30] and brain structural asymmetries in regions homologous with human language-relevant regions [31] . Furthermore, the direction of hand preference for clapping explains a significant portion of the variability in asymmetries of the planum temporale and inferior frontal gyrus [30] .…”
Section: Asymmetries In the Human Brain And In Our Primate Relativesmentioning
confidence: 99%
See 1 more Smart Citation